Analisis Yuridis Pelanggaran Merek Terhadap Pemegang Hak Merek Hugo Boss - I Nyoman Putu Budiartha; Anak Agung Rosiana Dewi Putri; Desak Gde Dwi Arini (Warmadewa Press, 2025)
One form of intellectual work that plays an important role in the trading business is a brand or branding. Trademarks are useful both as icons and as differentiators between goods or services in the trading business. The formulation of the problem in this study, namely: How is the regulation of HUGO BOSS trademark rights holders. How is the Judge's consideration of trademark infringement against HUGO BOSS trademark rights holders through Decision Number: 520 K/Pdt. Sus-HKI/2021 being researched This study applies normative legal research methods with a focus on statutory analysis and conceptual approaches. The results of this research show that in the case of HUGO BOSS versus Antony Tan, the defendant, Antony Tan, has committed infringement by imitating the HUGO BOSS trademark term without permission, which resulted in a legal dispute. HUGO BOSS but the lawsuit in the first HUGO BOSS verdict was rejected by the Supreme Court because it was considered that there was still the distinguishing power of the defendant's trademark so that HUGO BOSS also filed a cassation application. Preferably, if you want to register a brand, make a brand that is different from the brand name, logo, and has a difference in the quality of goods with existing brands or already registered at the Directorate General of Intellectual Property Rights (DJKI).